2019
DOI: 10.1007/s00268-019-04918-y
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Colo‐anal Anastomosis for Rectal Cancer: Pelvic Morbidity, Functional Results and Oncological Outcomes: A Systematic Review

Abstract: Background Delayed colo-anal anastomosis (DCAA) has received renewed interest thanks to its reduction in anastomotic leakage rate without the use of stoma to protect a low rectal anastomosis. The aim of this review was to summarize the available literature on DCAA following rectal cancer resection and to report clinical, oncological and functional results. Methods A comprehensive literature review was conducted including MEDLINE/Pubmed, EMBASE, SCOPUS, clinicaltrials.gov and the Cochrane database of systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
(126 reference statements)
3
22
0
Order By: Relevance
“…In one 2019 review by Portale et al involving eight studies where patients underwent the T-C technique for rectal cancer, the reported rates of anastomotic leak and pelvic abscess ranged between 0-10.6% and 0-25%, respectively. 20 In the current study, the observed rates of anastomotic leakage (4.5%) and pelvic abscess (4.5%) were in line with previous reports. In studies analysing patients undergoing CAA with protective ileostomy due to rectal cancer, the reported figures for anastomotic leakage and pelvic abscess ranged between 3-20% and 3-10.5%, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In one 2019 review by Portale et al involving eight studies where patients underwent the T-C technique for rectal cancer, the reported rates of anastomotic leak and pelvic abscess ranged between 0-10.6% and 0-25%, respectively. 20 In the current study, the observed rates of anastomotic leakage (4.5%) and pelvic abscess (4.5%) were in line with previous reports. In studies analysing patients undergoing CAA with protective ileostomy due to rectal cancer, the reported figures for anastomotic leakage and pelvic abscess ranged between 3-20% and 3-10.5%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In one 2019 review by Portale et al . involving eight studies where patients underwent the T–C technique for rectal cancer, the reported rates of anastomotic leak and pelvic abscess ranged between 0–10.6% and 0–25%, respectively 20 . In the current study, the observed rates of anastomotic leakage (4.5%) and pelvic abscess (4.5%) were in line with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…The literature shows good results with DCAA compared with immediate coloanal anastomosis with or without a J-pouch: Olagne et al [23] showed 70% good functional results at 2 years on 35 patients receiving 45 Gy and DCAA for low rectal cancer in accordance with Sage et al [24] and Jarry et al [21]. In a recent systematic review on DCAA for rectal cancer, Portale et al [25] reported poor faecal continence in less than 30% of patients. Preoperatively, patients are informed about these functional outcomes and postoperative rehabilitation programme and these elements are part of the decision process between restorative surgery and definitive stoma, especially for elderly patients.…”
Section: Discussionmentioning
confidence: 77%
“…[19][20][21][22][23] In the last 2 decades, this technique has been reintroduced for the treatment of rectal cancer when trying to avoid diverting stoma and its related morbidity, with promising results. 20,[24][25][26] Two systematic reviews 27,28 studying results of transanal colonic pullthrough with 2-stage coloanal anastomosis for low rectal cancer showed a low rate of anastomotic leak, low pelvic morbidity, and low use of stoma, with reasonably good functional results. However, evidence of the advantages of the Turnbull-Cutait pull-through with 2-stage hand-sewn coloanal anastomosis (TCA) over standard hand-sewn coloanal anastomosis associated with diverting lateral ileostomy (CAA) in rectal cancer is scarce.…”
mentioning
confidence: 99%